The Effect of Vulcanic Ash as a Nutrition Element on The Growth of Mustard Greens Varieties (Brassica juncea L. Var. Tosakan) - Hasanah, Aminatul Qomariyah; Yuliani, Yuliani (LenteraBio : Berkala Ilmiah Biologi, 2025)
Volcanic ash is a solid material in the form of dust released when a volcano erupts. Volcanic ash contains nutrients such as nitrogen, phosphorus, potassium, and a C/N ratio that encourages plant growth. The purpose of this study was to describe the content of nitrogen, phosphorus, and C/N ratio in volcanic ash, to test the effectiveness of volcanic ash administration, and to determine the optimal dose to influence the growth of mustard green plants. This study used an experimental design of a one-factor Randomized Block Design, namely the administration of volcanic ash with different doses to mustard green plants. Treatments A (control), B (125 grams), C (250 grams), D (375 grams), and E (500 grams). The growth parameters observed were plant height, number of leaves, total wet biomass, and wet biomass consumption. Data were analyzed using one-way ANOVA followed by the Duncan test. Based on the results of the study, volcanic ash contains nutrients N (0.31%) (Moderate); P (<0.0074%) (Deficient); and C/N ratio (1.84) (Meager). The administration of volcanic ash dose significantly affected all observed parameters. Treatment with a dose of 500 grams showed the best results on the growth of mustard green plants.